Providing a Framework for VR Functions in the Customer Journey of B2B Businesses - Zahra Nikoosefat Rad; Pejman Jafary; Farid Ahmadi (International Journal of Management, Accounting and Economics)
The growing adoption of virtual reality (VR) technology offers substantial opportunities for business-to-business (B2B) enterprises; however, its functions within the customer journey have not been thoroughly examined. This research aims to develop a comprehensive framework that highlights the application of VR throughout the customer purchasing journey, addressing the gaps and underutilization of this technology in B2B settings. To accomplish this, a thematic analysis of 37 relevant articles was performed, leading to the identification of six primary functions and 21 subfunctions of VR across different stages of the customer journey. In the pre-purchase stage, VR serves three functions: digital marketing communication, virtual meetings, and product development optimization, alongside nine subfunctions. During the purchase phase, VR functions as a decision support tool. In the post-purchase stage, two functions are identified: training for employees and customers, and optimization of maintenance processes, alongside eleven subfunctions. The findings indicate that VR is particularly effective in the pre-purchase stage, offering valuable implications for researchers, managers, and marketing professionals. By strategically leveraging these identified functions, B2B enterprises can enhance customer satisfaction and improve overall sales performance.